Breaking the Threads of Inequality: Gender Discrimination in Bangladesh's Garment Industry (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
This qualitative study explores the pervasive issue of gender discrimination within Bangladesh's garment industry, where women make up the majority of the workforce yet continue to face significant barriers to equality. Through in-depth interviews and surveys with 100 female workers from various garment factories in Dhaka, Chittagong, and other hubs, the research examines key forms of gender discrimination, including wage disparity, limited career advancement, workplace harassment, and the emerging threat of automation. The findings reveal that female workers earn significantly lower wages than their male counterparts, experience limited promotion opportunities, and endure high levels of sexual harassment, often compounded by a culture of silence and fear. Additionally, the rise of automation in the sector poses a unique challenge for women, with many fearing job displacements due to their lower skill levels in handling new technologies. The study concludes with actionable recommendations for addressing these issues, including implementing equal pay policies, establishing career development programs, enforcing anti-harassment measures, and providing gender-sensitive automation training. By highlighting the lived experiences of women workers, this research underscores the urgent need for comprehensive reforms to promote gender equality in Bangladesh’s garment sector.